Recurrent strangulated hernia of the right hemidiaphragm - V. I. Podoluzhnyi; A. B. Startsev; I. A. Radionov (Фундаментальная и клиническая медицина, 2022)
A multimodal approach to prevent the cognitive impairment in patients with cardiovascular diseases combines the control of major cardiovascular risk factors, cognitive recovery, and physical training. Here we discuss current advances in computer-aided (also called computer-assisted) cognitive recovery to prevent the cognitive impairment in patients with cardiovascular diseases, as this approach has a number of advantages in comparison with the conventional tools. We describe a cognitive training software to stimulate perception, attention, short-term memory, executive functions, speech, and thinking. Baseline neurological examination and neuropsychological testing are mandatory before starting a cognitive recovery. A particular attention is paid to the high prevalence of cognitive impairment in cardiac surgery patients. Around half of them have pre-operative cognitive impairments, and almost half of the patients suffer from a postoperative cognitive dysfunction. Among the brain regions, prefrontal and parietal cortex and hippocampus are the most sensitive to circulatory disorders as they are supplied by the terminal branches of the cerebral arteries. Therefore, cognitive rehabilitation of cardiac surgery patients should include computer-aided cognitive training tasks activating these brain regions.